(untitled) (Research, Society and Development, 2024)
Introduction: Hemophagocytic lymphohistiocytosis (HLH) is a rare inflammatory syndrome that primarily affects children. It can be caused by both genetic mutations and external factors such as Epstein-Barr virus (EBV) infection. The aim of this study is to elucidate the known aspects of this condition and emphasize the need for further studies on diagnostic and therapeutic methods. Methodology: This is an integrative review on EBV-associated HLH. Data was collected from the Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO), and National Library of Medicine (PubMed) databases, using the descriptors "EBV Infections," "Hemophagocytic Lymphohistiocytosis," and "Pediatrics" to address the question formulated through the PICO strategy. Results and Discussion: HLH is divided into primary, which is associated with genetic mutations, and secondary, which depends on triggers such as infections, autoimmunity, and neoplasms. Among secondary HLH, EBV-triggered HLH stands out, which is generally self-limiting like infectious mononucleosis but can lead to an uncontrolled immune response through T cell activation and stimulation of pro-inflammatory factors with systemic repercussions. Fever, associated with abdominal pain and hyperferritinemia, should raise the diagnostic hypothesis. There are treatment protocols, but new drugs are showing good responses according to the literature. Conclusion: EBV-associated HLH is a rare and potentially fatal condition, representing a significant diagnostic challenge. New research is essential for more effective diagnosis, therapy, and improved prognoses.